2023
DOI: 10.1101/2023.10.10.561760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphoglycerate kinase 1 is a central leverage point in Parkinson's disease driven neuronal metabolic deficits

Alex Kokotos,
Aldana Antoniazzi,
Santiago Unda
et al.

Abstract: Phosphoglycerate kinase 1 (PGK1), the first ATP producing glycolytic enzyme, has emerged as a therapeutic target for Parkinson's Disease (PD), since a potential enhancer of its activity was reported to significantly lower PD risk. We Carried out a suppressor screen of hypometabolic synaptic deficits and demonstrated that PGK1 is the rate limiting enzyme in nerve terminal ATP production. Increasing PGK1 expression in mid-brain dopamine neurons protected against hydroxy-dopamine driven striatal dopamine nerve te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…It is notable that despite the greater respiratory capacity in inhibitory axons, the dynamics of ATP changes during intense electrical stimulation in glucose were similar to those seen in excitatory axons (Figure 2A). Both the activity driven ATP deficit (Figure 2B) and recovery following stimulation (Supplementary Figure 1B) were similar in the two neuron classes, suggesting that acute ATP dynamics are governed largely by glycolysis, consistent with our recent discovery that the first ATP producing enzyme in glycolysis (phospoglycerate kinase 1) is rate limiting (Kokotos et al, 2023). The lack of a difference in excitatory and inhibitory ATP recovery rates following stimulation even in conditions of metabolic compromise (Supplementary Figure 1C, 1D, 1F) suggests that ATP consumption and production rates during and directly following stimulation are similarly well equipped to meet metabolic need in excitatory and inhibitory neurons.…”
Section: Discussionsupporting
confidence: 88%
“…It is notable that despite the greater respiratory capacity in inhibitory axons, the dynamics of ATP changes during intense electrical stimulation in glucose were similar to those seen in excitatory axons (Figure 2A). Both the activity driven ATP deficit (Figure 2B) and recovery following stimulation (Supplementary Figure 1B) were similar in the two neuron classes, suggesting that acute ATP dynamics are governed largely by glycolysis, consistent with our recent discovery that the first ATP producing enzyme in glycolysis (phospoglycerate kinase 1) is rate limiting (Kokotos et al, 2023). The lack of a difference in excitatory and inhibitory ATP recovery rates following stimulation even in conditions of metabolic compromise (Supplementary Figure 1C, 1D, 1F) suggests that ATP consumption and production rates during and directly following stimulation are similarly well equipped to meet metabolic need in excitatory and inhibitory neurons.…”
Section: Discussionsupporting
confidence: 88%
“…In a second approach, we used a synaptic endurance assay that we recently developed where neurons are subjected to repeated rounds of stimulation at minute intervals ( Kokotos et al, 2023 ). We previously showed that under sufficient glycolytic fuel conditions, excitatory neurons are capable of sustaining at least ten rounds of stimulation without a significant slowing of SV recycling ( Kokotos et al, 2023 ). Here, we found that both excitatory and inhibitory neurons can sustain synaptic function under this paradigm when fueled by either lactate and pyruvate or BHB ( Figure 3A , 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the downregulated gene, MDMA promotes MALAT1 expression and inhibits the targeted downregulation of MEKK3 by miR-124, resulting in upregulation of the expression of MEKK3 and finally jointly promoting PD progression (24). In PD induced neuronal metabolic deficits, phosphoglycerate kinase (PGK1) serves as a crucial focal point (25). Moreover, it has been shown that inhibition of prolyl hydroxylase is a promising therapeutic strategy for PD through improving the mitochondrial function under oxidative stress (26).…”
Section: Isogenic Control Single Cells Against Pd Single Cellsmentioning
confidence: 99%